Keberadaan Serangga Perusak Daun Pada Enam Kultivar Ubi Jalar (Ipomoea batatas L) - Wahid, Mujaddid Muskhul; Haryanto, Hery; Supeno, Bambang (LPPM Institut Pendidikan Nusantara Global, 2025)
Sweet potato (Ipomoea batatas L.) is a type of cultivated plant whose roots form tubers with high nutritional content, especially carbohydrates. This study aimed to identify the presence of leaf-damaging insects during the growth of sweet potato (Ipomoea batatas L.). The research used an experimental method and was designed using a Randomized Complete Block Design (RCBD) consisting of 6 sweet potato cultivar treatments (KUJ), namely Lato-lato (KUJ1), Cilembu (KUJ2), Thailand (KUJ3), Kentang (KUJ4), Ase (KUJ5), and Purple (KUJ6). Each treatment was repeated 4 times, resulting in 24 experimental units. The results of the study revealed the presence of six leaf-damaging insects: whiteflies, grasshoppers, leafrollers, armyworms, tortoise beetles, and leafminers. The leafroller was the most dominant pest, showing a significant population surge, especially in the 9th week after planting (9 WAP), particularly on the Ase cultivar. Afterwards, its population declined significantly in the 11th week after planting (11 WAP). The KUJ6 (Purple) treatment had the highest diversity index at 1.10. KUJ6 (Purple) also had the highest evenness value at 0.62, while the highest dominance value, 0.28, was found in the KUJ4 (Kentang) treatment.